Degree of the application governance principles for governance of the state’s administrative in light of the requirements of the Oman vision (2040) = درجة تطبيق مبادئ الحوكمة بالجهاز الاداري للدولة في ضوء رؤية عمان 2040 - Al-Fathi, Khalifa Mohammed Said; Al-Hidabi, Dawood Abdulmalek Yahya (International e-Journal of Advances in Social Sciences, (IJASOS), 2020)
This quantitative study discusses the principles of governance in the state’s administrative apparatus, in light of Oman’s vision (2040). As the global governance indicators indicated by the World Bank in (2017) pointed to the ranking of the Sultanate of Oman in the ranks (61 to 81) in indicators: political stability and absence of violence, rule of law, government efficiency, organizational quality, and control of corruption. Therefore, the study aims to diagnose the degree of application of the principles of governance in the state’s administrative apparatus, in light of Oman’s vision (2040). The descriptive approach was used, and the sample size reached (400) employees from the administrative apparatus in the Sultanate of Oman. The researcher adopted a questionnaire consisting of (28) phrases distributed in (5) axes. The results concluded that all five axes came in (intermediate) grades; arithmetic averages ranged from (2.34) to (3,66). *************************************************** تناقش هذه الدراسة الكمية؛ مبادئ الحوكمة بالجهاز الإداري للدولة، في ضوء رؤية عمان (2040). حيث أشارتْ مؤشرات الحوكمة العالمية الصارة عن البنك الدولي عام (2017) إلى تصنيف سلطنة عُمان في المراكز (61 إلى 81) في مؤشرات: الاستقرار السياسي وغياب العنف، سيادة القانون، الكفاءة الحكومية، الجودة التنظيمية، السيطرة على الفساد. لذا تهدف الدراسة إلى تشخيص درجة تطبيق مبادئ الحوكمة بالجهاز الإداري للدولة، في ضوء رؤية عمان (2040). تم استخدام المنهج الوصفي، وبلغ حجم العينة (400) موظف من العاملين بالجهاز الإداري في سلطنة عمان. اعتمد الباحث استبانة مكونة من (28) عبارة موزعة في (5) محاور. توصلت النتائج إلى أن كافة المحاور الخمس جاءت بدرجات (متوسطة)؛ تراوحت المتوسطات الحسابية من (2,34) إلى (3,66)